Effectiveness of Quantom Kit as a Supplementary Learning Material in Enhancing the Academic Performance - Manilyn M. Galarosa; Ofelia Maningas; Karen A. Manaig; Rolando Maningas; Alberto D. Yazon (Advanced Journal of STEM Education, 2024)
Science education benefits greatly from the supplementary learning materials that provide hands-on, interactive experiences, enhancing student engagement and understanding scientific concepts. This study evaluated the effectiveness of the Quantom Kit as a supplementary learning material to improve the academic performance of Grade 8 students at Looc Integrated School. Using a quasi-experimental design, 50 students were divided into two groups: an Experimental group that used the QuanTom Kit and a Comparison group that relied solely on the Periodic Table. Results showed that the Experimental group consistently outperformed the Comparison group in pretests, posttests, and six formative tests. Independent Samples T-tests revealed a significant difference in mean scores between the groups (p < .01), confirming the Quantom Kit’s positive impact on student performance. Paired Sample t-tests also demonstrated significant improvements in mean scores between pretest and post-tests within each group. While both groups showed improvement, the Experimental group achieved significantly higher post-test scores and larger effect sizes, highlighting the Quantom Kit’s effectiveness in enhancing academic performance. This study underscores the value of incorporating interactive learning materials into science education to enhance student achievement.